2009
DOI: 10.3324/haematol.2009.007005
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dense and high-dose chemotherapy plus rituximab with autologous stem cell transplantation for primary treatment of diffuse large B-cell lymphoma with a poor prognosis: a phase II multicenter study

Abstract: BackgroundWe investigated the addition of rituximab to dose-dense and high-dose chemotherapy with autologous stem cell transplantation in patients with untreated poor-prognosis diffuse large B-cell lymphoma. Design and MethodsNinety-four young patients (age, 18-60) with stage III-IV diffuse large B-cell lymphoma at intermediate/high or high risk according to the age-adjusted International Prognostic Index were enrolled into a phase II trial. The treatment was as follows: four courses of bi-weekly rituximab-cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 42 publications
2
37
0
1
Order By: Relevance
“…190 patients (97%) in the R-ACVBP group received the fi rst four cycles of the planned treatment and 177 (97%) in the R-CHOP group. The median interval between these cycles was 14 days (range 12-57, IQR [14][15][16][17] in the R-ACVBP group and 21 days in the R-CHOP group. Based on data collected from the population who received the fi rst four cycles of each treatment, the received dose intensities for doxorubicin were 92·1%, for cyclophosphamide were 93·0%, and for rituximab were 92·3% of the planned dose for R-ACVBP, and 98·4%, 98·6%, and 98·6% for R-CHOP, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…190 patients (97%) in the R-ACVBP group received the fi rst four cycles of the planned treatment and 177 (97%) in the R-CHOP group. The median interval between these cycles was 14 days (range 12-57, IQR [14][15][16][17] in the R-ACVBP group and 21 days in the R-CHOP group. Based on data collected from the population who received the fi rst four cycles of each treatment, the received dose intensities for doxorubicin were 92·1%, for cyclophosphamide were 93·0%, and for rituximab were 92·3% of the planned dose for R-ACVBP, and 98·4%, 98·6%, and 98·6% for R-CHOP, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, several phase 2 trials have shown promising results regarding the association of intensive chemotherapy and rituximab. [16][17][18][19] Most of these regimens were proposed for patients with high-risk disease and contained an intensive chemotherapy schedule with stem-cell support. [16][17][18] By contrast, dose-adjusted EPOCH (etoposide, prednisone, vincristine, cyclophosphamide, and doxorubicin) is an intensifi ed regimen where pharma codynamic dosing is on the basis of neutrophil nadir.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13] Data for patients with 3 or more IPI factors treated with R-CHOP from the British Columbia registry suggest a 4-year progressionfree survival (PFS) at 53%, 1 in agreement with the 58% 3-year PFS seen in several German randomized studies. 14 However, very few prospective studies have been reported on large series focusing on DLBCL with 2 or 3 aa-IPI factors with a long follow up 15,16 in a population under 60 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…2,[9][10][11] Indeed, as the median age of patients diagnosed with DLBCL is in the mid-60s, 1,12,13 many older individuals and others with comorbidities are in particular need of better initial therapy because they cannot tolerate intensive salvage chemotherapy with stem cell transplantation. 14 Novel therapeutic approaches beyond rituximab are, therefore, still required.…”
Section: Introductionmentioning
confidence: 99%